An Alternative Nested Reading Frame May Participate in the Stress-Dependent Expression of a Plant Gene - Sheshukova, Ekaterina V.; Komarova, Tatiana V.; Ershova, Natalia M.; Shindyapina, Anastasia V.; Dorokhov, Yuri L. (Frontiers in Plant Science, 2017)
Although plants as sessile organisms are affected by a variety of stressors in the field, the stress factors for the above-ground and underground parts of the plant and their gene expression profiles are not the same. Here, we investigated NbKPILP, a gene encoding a new member of the ubiquitous, pathogenesis-related Kunitz peptidase inhibitor (KPI)-like protein family, that we discovered in the genome of Nicotiana benthamiana and other representatives of the Solanaceae family. The NbKPILP gene encodes a protein that has all the structural elements characteristic of KPI but in contrast to the proven A. thaliana KPI (AtKPI), it does not inhibit serine peptidases. Unlike roots, NbKPILP mRNA and its corresponding protein were not detected in intact leaves, but abiotic and biotic stressors drastically affected NbKPILP mRNA accumulation. In search of the causes of suppressed NbKPILP mRNA accumulation in leaves, we found that the NbKPILP gene is “matryoshka”, containing an alternative nested reading frame (ANRF) encoding a 53-amino acid (aa) polypeptide (53aa-ANRF) which has an amphipathic helix (AH). We confirmed ANRF expression experimentally. A vector containing a GFP-encoding sequence was inserted into the NbKPILP gene in frame with 53aa-ANRF, resulting in a 53aa-GFP fused protein that localized in the membrane fraction of cells. Using the 5'-RACE approach, we have shown that the expression of ANRF was not explained by the existence of a cryptic promoter within the NbKPILP gene but was controlled by the maternal NbKPILP mRNA. We found that insertion of mutations destroying the 53aa-ANRF AH resulted in more than a two-fold increase of the NbKPIL mRNA level. The NbKPILP gene represents the first example of ANRF functioning as a repressor of a maternal gene in an intact plant. We proposed a model where the stress influencing the translation initiation promotes the accumulation of NbKPILP and its mRNA in leaves.